Sustainable and integrated urban planning and governance in metropolitan and medium-sized cities - Medeiros, E. (2020)
This paper examines the design and implementation process of Integrated Strategies for Sustainable Urban Development (ISUD), as well as their main effects and lessons learned in two European cities: Barcelona in Spain, a vibrant European metropolis, and Évora in Portugal, a medium-sized city with a world heritage historic centre. The former is facing socioeconomic challenges in some of its neighbourhoods, while the latter, a regional capital of an already depopulated region, Alentejo, is facing further depopulation and socioeconomic challenges. Following from a qualitative analysis of ISUD and other urban plans implemented in past decades, the article employs a framework with five analytical dimensions, based on the policy cycle (priority setting, participatory approaches, implementation strategy, collaboration networks, and measuring results and impact). These provide a framework to identify best practices. The findings demonstrate that ISUD in both cities provides impetus for sustainable strategic planning, but can be strengthened in particular via the active involvement of citizens and stakeholders in the elaboration and implementation of these ISUD. Conversely, the results demonstrate mounting challenges that many urban planners in medium-sized towns face in relation to inverting depopulation trends, raising further questions of to what extent European Cohesion policy, and ISUD in particular, can contribute to territorial cohesion objectives whilst also aiming to achieve other policy goals.